PEMBUATAN SISTEM PENGGERAK MESIN CETAK PELET IKAN - Habib Ramadhan, Muhammad; Sulaiman, Sulaiman; Eka Putra, Ismet (Jurnal Teknologi dan Vokasi, 2025)
The fisheries industry is one of the important sectors in the Indonesian economy. One crucial aspect in fish farming is the provision of high-quality and continuous feed. Fish pellets are the main choice because of their balanced nutritional content and ease of use. So far, fish pellets available on the market are often imported from large producers who dominate the market. Therefore, an alternative solution is needed that allows farmers to produce their own fish pellets with reliable quality and more economical costs. The creation of a drive system on a fish pellet molding machine is an effort to increase the efficiency of producing quality and affordable fish feed. The working principle of this drive system uses a mechanical energy conversion mechanism from an electric motor to the grinding and molding components. The electric motor functions as the main source of power, which is then transmitted through a gear or belt system to the grinding section to crush raw materials and mold pellets according to the desired size. The process of making the drive system involves calculating the engine pulley rotation of 1400 rpm while the driven pulley rotation is 437.5 rpm, the belt speed is 464 cm / s and the torque is 1,660.80 kg.mm. The test results show that the machine is capable of producing pellets after 3 tests with variations in the weight of the pellet raw materials, the results of the first test were 15.65 kg/hour, the second test 26.47 kg/hour and the third 26.67 kg/hour and the average result was 68.79 kg/hour.